PENGARUH ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE DISCLOSURE TERHADAP FINANCIAL SUSTAINABILITY DENGAN FINANCIAL PERFORMANCE SEBAGAI VARIABEL MODERASI - Mikael Valdheerian Barnix; Yeni Januarsi; Nurhayati Soleha (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to determine the effect of environmental, social, and governance disclosure (ESG disclosure) on financial sustainability with financial performance as a moderating variable. This study uses stakeholder theory to explain the problems of this study. The population used in this study uses companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023 consisting of the Energy, Industrials, Consumer Non-Cyclicals, Consumer Cyclicals and Basic Materials sectors. The sample selection technique used in this study uses the purposive sampling method with a total sample of 275 companies. The data analysis technique for this study uses time-series cross sectional pooled ordinary least squares regressions with standards error clustered by No and Year, with STATA v18 software. The results of this study indicate that ESG disclosure has a positive effect on financial sustainability. Likewise, each environmental, social, and governance disclosure has a positive effect on financial sustainability. In contrast to the moderating role of financial performance which has no moderating effect on the relationship between ESG disclosure and financial sustainability. Likewise, financial performance has no moderating effect on the relationship between environmental, social, and governance disclosures and financial sustainability.